Modern Agricultural Technology and Rural Development in Sri Lanka: A Case Study of TRINCAP Project in Trincomalee District - Navaratnam, J. (My University, 2011)
This research has scrutinized the modem agriculture technology and rural development via core farmer practices. The targeted area of this study consists of five Grama Niladhari Divisions from Morawewa, Thampalagamam, and Kuchcheveli Divisional Secretariat Divisions in Trincomalee District. The objectives of this research were to measure the contributory factors, which limit the spread of modem technology and agricultural development, how to popularize modem technology in rural areas in a sustainable manner with participatory approach, and how to utilize the rural resources at optimum level. For achieving these objectives, the study was used multi dimensional approaches, with the employment of both quantitative and qualitative research methods. Also relevant data for the study were gathered from the secondary as well as primary sources. The main primary data collection methods were questionnaire survey from 50 samples, and some interviews were conducted by use of questionnaires on qualitative and quantitative aspects, key informant interviews were held with the government officers, officials of TRINCAP-JICA, some beneficiaries of the TRINCAP projects and others. Primary date was processed by using relevant qualitative analysis methods, and the SPSS package was utilized for qualitative data analysis. This study was aware several institutions disseminate modem agricultural technology in the rural areas of the country, but training and services were not reached sufficiently to the rural farmers. Also most of the farmers were not adopted the emerging scientific knowledge in their farming activities due to lack of knowledge, and skills. During the study, it was identified that the training programme and study tours are most essential to acquire modem agricultural technologies by rural farmers. It was found, that the Core Farmer practices playa significant role in disseminate relevant modem agricultural technologies among the farmers and surrounding areas and supported to rural development process. It was identified, that the deficiencies in government delivery mechanism in respect of modem agricultural technologies by agriculture extension services, and it is very essential to acquire knowledge and skills from time to time.